2010
DOI: 10.1002/jmri.22234
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the neck at 3 Tesla using the periodically rotated overlapping parallel lines with enhanced reconstruction (PROPELLER) (BLADE) sequence compared with T2‐weighted fast spin‐echo sequence

Abstract: Purpose: To evaluate motion artifacts, tissue contrasts, and lesion detectability in the neck with the periodically rotated overlapping parallel lines with enhanced reconstruction (PROPELLER) (BLADE) technique. Materials and Methods:A total of 46 patients referred for MRI of the neck were included in a comparison of T2-weighted BLADE (T2W-BLADE) sequence and T2W fast spin-echo (T2W-FSE) sequence. All examinations were performed at 3T using the same parameters. Two observers evaluated unlabelled images for moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…[3,8] Other studies showed that the method also improved the anatomical imaging (T1W or/and T2W) of cardiac, lungs, and head and neck by motion reduction. [6,9,12,14] Our study is the first to report that the severity of respiration and peristalsis induced artifacts on bladder imaging can be compensated by using PROPELLER, which appears to be a valuable tool to ensure consistent diagnostic image quality.…”
Section: Discussionmentioning
confidence: 91%
“…[3,8] Other studies showed that the method also improved the anatomical imaging (T1W or/and T2W) of cardiac, lungs, and head and neck by motion reduction. [6,9,12,14] Our study is the first to report that the severity of respiration and peristalsis induced artifacts on bladder imaging can be compensated by using PROPELLER, which appears to be a valuable tool to ensure consistent diagnostic image quality.…”
Section: Discussionmentioning
confidence: 91%
“…For the second case of bipolar motion, the blades gather around two principal locations as anticipated. For group1, it includes blade 1,6,7,12,13,14,19,20 if counting from left to right and top to bottom; group 2 includes blade 2, 3,4,8,9,10,11,15,16,17,18. Blade 5 suffers from severe corruption.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The data in this circular area are then used as reference data for rigid motion correction of both rotation and translation. This technique offers intrinsic advantages over other methods with respect to patient motion, thus it has attracted significant clinical adoption (1,(3)(4)(5)(6)(7). Because of its inherent reduced sensitivity to various sources of image artifacts, such as B0-related artifacts in EPI techniques, PROPELLER has also been used for diffusion MR imaging (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Third, the HEP sequence would be applicable not only for the carotid plaque imaging but also for other applications. Indeed, Ohgiya et al have reported that PROPELLER is a good method for obtaining motion‐insensitive high‐quality imaging for lesion detection in the neck. However, they simultaneously described that the major disadvantage of PROPELLER in the neck is the occasional degradation of image quality due to streak artifacts.…”
Section: Discussionmentioning
confidence: 99%